Atmosphere-dependent stability and mobility of catalytic Pt single atoms and clusters on γ-Al2O3. Issue 14 (26th March 2019) - Dessal, Caroline; Sangnier, Alexis; Chizallet, Céline; Dujardin, Christophe; Morfin, Franck; Rousset, Jean-Luc; Aouine, Mimoun; Bugnet, Matthieu; Afanasiev, Pavel; Piccolo, Laurent
Abstract : Pt single atoms, stable on alumina under O2, form mobile clusters under H2, due to adsorbate- and nuclearity-dependent metal-support interaction. Abstract : Atomically dispersed metals promise the ultimate catalytic efficiency, but their stabilization onto suitable supports remains challenging owing to their aggregation tendency. Focusing on the industrially-relevant Pt/γ-Al2 O3 catalyst, in situ X-ray absorption spectroscopy and environmental scanning transmission electron microscopy allow us to monitor the stabilization of Pt single atoms under O2 atmosphere, as well as their aggregation into mobile reduced subnanometric clusters under H2 . Density functional theory calculations reveal that oxygen from the gas phase directly contributes to metal-support adhesion, maximal for single Pt atoms, whereas hydrogen only adsorbs on Pt, and thereby leads to Pt clustering. Finally, Pt cluster mobility is shown to be activated at low temperature and high H2 pressure. Our results highlight the crucial importance of the reactive atmosphere on the stability of single-atom versus cluster catalysts.